Hang the Moon: A Novel (Written in the Stars, ,, 2021)
In a delightful follow-up to Written in the Stars, Alexandria Bellefleur delivers another #ownvoices queer rom-com about a hopeless romantic who vows to show his childhood crush that romance isn't dead by recreating iconic dates from his favorite films.... Brendon Lowell loves love. It's why he created a dating app to help people find their one true pairing and why he's convinced "the one" is out there, even if he hasn't met her yet. Or... has he? When his sister's best friend turns up in Seattle unexpectedly, Brendon jumps at the chance to hang out with her. He's crushed on Annie since they were kids, and the stars have finally aligned, putting them in the same city at the same time. Annie booked a spur-of-the-moment trip to Seattle to spend time with friends before moving across the globe. She's not looking for love, especially with her best friend's brother. Annie remembers Brendon as a sweet, dorky kid. Except, the 6-foot-4 man who shows up at her door is a certified Hot Nerd and Annie.... wants him? Oh yes. Getting involved would be a terrible idea-her stay is temporary and he wants forever-but when Brendon learns Annie has given up on dating, he's determined to prove that romance is real. Taking cues from his favorite rom-coms, Brendon plans to woo her with elaborate dates straight out of Nora Ephron's playbook. The clock is ticking on Annie's time in Seattle, and Brendon's starting to realize romance isn't just flowers and chocolate. But maybe real love doesn't need to be as perfect as the movies... as long as you think your partner hung the moon.

Count Your Lucky Stars: A Novel (Written in the Stars, ,, 2022)
Margot Cooper doesn't do relationships. She tried and it blew up in her face, so she'll stick with casual hookups, thank you very much. But now, her entire crew has found "the one" and she's beginning to feel like a fifth wheel. And then, fate (the heartless bitch) intervenes. While touring a wedding venue with her engaged friends, Margot comes face-to-face with Olivia Grant, her childhood friend, her first love, her first...well, everything. It's been ten-years, but the moment they lock eyes, Margot's cold, dead heart thumps in her chest. Olivia must be hallucinating. In the decade since she last saw Margot, her life hasn't gone exactly as planned. At almost thirty, she's been married...and divorced. However, a wedding planner job in Seattle means a fresh start and a chance to follow her dreams. Never in a million years did she expect her important new client's Best Woman would be the one that got away. When a series of unfortunate events leaves Olivia without a place to stay, Margot offers up her spare room because she's a Very Good Person. Obviously. It has nothing to do with the fact that Olivia is as beautiful as ever and the sparks between them still make Margot tingle. As they spend time in close quarters, Margot starts to question her no-strings stance. Olivia is everything she's ever wanted, but Margot let her in once and it ended in disaster. Will history repeat itself or should she count her lucky stars that she gets a second chance with her first love?